Kinerja Keuangan dan Praktik Keberlanjutan: Peran Moderasi Ukuran Perusahaan Sektor Industrials 2020-2023 - Salsabilah, Imroatus; Astuti, Suryani Yuli; Febrianti, Devi; Imawan, Amrizal (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Sustainability-oriented companies do not solely focus on profit generation but also strive to balance financial, social, and environmental dimensions. This study aims to analyze the influence of green accounting, environmental performance, and corporate social responsibility (CSR) on financial performance, as well as the moderating role of firm size. The research object includes industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A quantitative approach with an associative design based on secondary data was employed. The sampling technique used was purposive sampling, resulting in 148 observation samples. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 3 software. The findings reveal that green accounting does not significantly affect financial performance, as indicated by a p-value of 0.840. Meanwhile, environmental performance and CSR show positive and significant relationships with financial performance, with p-values of 0.032 and 0.024, respectively. Firm size does not moderate the relationships between the three exogenous variables and financial performance, with p-values of 0.845, 0.749, and 0.909. These results suggest that the success of sustainability implementation depends more on the quality of its execution rather than on the size of the company.